Możliwości wykorzystania informacji z księgi podatkowej przychodów i rozchodów w controllingu małego przedsiębiorstwa - Szydełko, Alfred (The Possibility of Using Information from Tax Book of Incomes and Outgoings in the Controlling of a Small Enterprise., 2006)
Tax book of incomes and outgoings is used to count tax bases of personal income tax (PIT). The records in this book depend upon the tax law. However, some of the information may be used for managing an enterprise, for example by counting profitability.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 217-223